2003
DOI: 10.1002/micr.10208
|View full text |Cite
|
Sign up to set email alerts
|

Administration of bone marrow cells into surgically induced fibrocollagenous tunnels induces angiogenesis in ischemic rat hindlimb model

Abstract: We established a comparative model of angiogenic induction in previously formed fibrocollagenous tunnels in rat inner thigh muscles. A unilateral hindlimb chronic ischemia model was performed in male Sprague-Dawley rats. A device was then inserted in the central portion of the inner thigh muscles. Vascularity in the ischemic limb was determined by means of an angiographic score, capillary/fiber ratio, and endothelial proliferation by histochemistry and immunohistochemistry. Autologous transplant of bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A limitation of the present study includes the PBMC treatment consisted in the administration of mononuclear cells preparation, where only 4% corresponded to CD34 + MPCs, but the remaining mononuclear cells were not characterized. Such portion of MPCs has been previously described as enough to significantly stimulate angiogenesis in the same experimental model (Padilla et al, ); however, the effects of additional factors present in the cell preparation were not assessed in the present study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A limitation of the present study includes the PBMC treatment consisted in the administration of mononuclear cells preparation, where only 4% corresponded to CD34 + MPCs, but the remaining mononuclear cells were not characterized. Such portion of MPCs has been previously described as enough to significantly stimulate angiogenesis in the same experimental model (Padilla et al, ); however, the effects of additional factors present in the cell preparation were not assessed in the present study.…”
Section: Discussionmentioning
confidence: 82%
“…PRP‐containing factors may interact with cell receptors related with the activation of endothelial cells, mesenchymal cells, and fibroblasts, which play a key role within the angiogenic response (Wahlberg, ). PBMC and MPC autologous transplants have been a secure and effective strategy to support revascularization, either in animal models or clinical trials of patients with advanced vascular disease (Aranguren, Verfaillie, & Lettun, ; Franz et al, ; Padilla et al, , ). Benoit et al () reported a meta‐analysis of 45 studies of transplanted autologous MPCs in population with lower limb critical ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen, particularly types I and III, induces angiogenesis, a phenomenon repeatedly observed in other studies in which collagen fiber tunnels or conduits have been used, with or without specific inducers. 10,11,18,19 In this experiment we assume that angiogenesis contributed to the increase in tracheal wall thickness at the implant site, which probably increased the structural support of the collagencovered mesh, thus avoiding its collapse.…”
Section: Discussionmentioning
confidence: 91%
“…The physicochemical and pharmacological properties of this copolymer are derived from its components. C–PVP exhibits immunomodulatory and tissue-regenerative properties, which have been evidenced in different pathologies in acute and chronic stages in various fields, including orthopedics and trauma, vascular surgery, gynecology and gastroenterology, as well as dermatology and rheumatology. …”
Section: Introductionmentioning
confidence: 99%